Power allocation under per-antenna power constraints in multiuser MIMO systems - Sheng-qian HAN; Chen-yang YANG (Tongxin xuebao)
A low-complexity power allocation algorithm was investigated under per-antenna power constraints(PAPC)in multiuser multiple-input multiple-output (MIMO) systems.It was shown that the optimal power allocation subject to PAPC,aimed at maximizing the sum rate of multiple users with zero forcing (ZF) precoders,had the structure of water-filling with multiple water-levels.Based on this result,the equivalence between PAPC and weighted sum power constraints was proved and a low-complexity suboptimal power allocation method was then proposed.Simulation results show that the proposed method outperforms the existing equal power allocation method and the heuristic method,and it can efficiently reduce the computational complexity with a negligible performance loss compared with the optimal power allocation method.